Substitution Analysis in Nutrition Sciences: A Tutorial - Doaei, Saeid; Mosavi Jarrahi, Alireza; Gholamalizadeh, Maryam; Nazarzadeh, Milad (Asian Pacific Journal of Cancer Biology, 2016)
Evaluating the effects of nutrients in our diet needs to enter more than one nutrient item (or food groups) in a single statistical unit. Accordingly, not only we consider the effects of a nutrient in health-related subjects, but also we find out the consequences of replacing and deleting nutrients. In nutritional epidemiology, substitutional analysis is used to evaluate the effects of various nutrients on a specific outcome. In the substitutional analysis, when some nutrients or foods are included in a single statistical model, investigation of the effects of several nutrients on the specific outcome is more achievable. The objective of this paper was to provide a detailed examination of the key aspects of substitutional analysis in nutritional sciences.